PENINGKATAN HASIL BELAJAR MENULIS KARANGAN NARASI MENGGUNAKAN METODE MENULIS BERANTAI KELAS IV SD - Aulya, Widya Ismi; Kaswari, Kaswari; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this research is describethe learning outcome in learning to use the type of Indonesia Language writing chain in class VB State Public Elementary School 34 Pontianak city . The method used in this research is descriptive method , the form of research is classroom action research , and the nature of research is collaborative. The results were obtained ( 1 ) . The performance of teachers in designing learning from the first cycle is 4,04, the second cycle is 4,81, and the third cycle is 4,81 ( 2 ) . The performance of teachers in implementing the learning of the first cycle is 3,61 , the second cycle is 4.16 , and the third cycle 4.55 ( 3 ) . On average the study of students increased from the first cycle of 69.03 into a 69,03 second cycle , and the cycle III, 76.87 . By applying a type of think pair share to improve learning outcomes in the classroom IPS VB State Elementary School 33 West Pontianak districts.Keywords:learning outcome, language learning indonesia, method writing chain